PENGARUH MEDIA SOSIAL DAN ELECTRONIC WORD OF MOUTH DALAM MENINGKATKAN LOYALITAS PELANGGAN PADA DLUXE NAILS - br Sinuraya, Dea Carera; Putra, Irwansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to determine the effect of social media and Electronic Word of Mouth in increasing customer loyalty at Dluxe Nails. This study uses a quantitative approach where the population in this study are Dluxe Nails customers recorded from January to December 2024, selected using purposive sampling. Data collection was conducted through questionnaires. The results of the study show that the influence of social media and Electronic Word of Mouth simultaneously has a significant effect on customer loyalty. The tests conducted show that social media and Electronic Word of Mouth partially have a positive and significant effect on customer loyalty. The Adjusted R Square value obtained from the Determinant Coefficient (R2) test on customer loyalty is 0.778, meaning that 77.8% can be explained by social media and Electronic Word of Mouth. Meanwhile, the remaining 22.2% can be explained by other factors not examined in this study.